Intravenous brexanolone for postpartum depression: what it is, how well does it work, and will it be used? - Justin Faden; Leslie Citrome (SAGE Publishing, 2020)
Postpartum depression is considered to be a subtype of major depressive disorder that occurs in approximately 10-20% of mothers worldwide. However, in actuality, these numbers are likely underreported due to minimization and the stigma of mental illness. Until recently, there were no approved medications for the treatment of postpartum depression. Allopregnanolone is a naturally occurring neuroactive steroid whose serum levels decline precipitously following childbirth. This hormonal fluctuation has been postulated as playing a role in the pathophysiology of postpartum depression. Brexanolone is the first medication approved by the US Food and Drug Administration for the treatment of postpartum depression. Brexanolone is an intravenous proprietary formulation of allopregnanolone that can be administered to produce stable serum levels comparable with third-trimester concentrations in postpartum mothers. It is hypothesized to modulate neuronal excitability by functioning as an allosteric modulator of γ-aminobutyric acid-A receptors and is administered under monitoring as a 60 h continuous infusion. In this review, we will highlight the results of the clinical trial program, including efficacy and tolerability data. Practical and logistical considerations of brexanolone will be reviewed, as will its potential place in therapy for the treatment of postpartum depression.